2016
DOI: 10.1111/sms.12724
|View full text |Cite
|
Sign up to set email alerts
|

The impact of remote ischemic preconditioning on cardiac biomarker and functional response to endurance exercise

Abstract: Abstract:Introduction. Remote ischaemic preconditioning (RIPC; repeated short reversible periods of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
27
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 43 publications
3
27
1
1
Order By: Relevance
“…As expected, we also demonstrated that RIPC can enhance exercise endurance during severe‐intensity exercise in this test. Several previous studies have reported the beneficial effect of RIPC on exercise performance, whereas other studies did not observe such effects . Of those, Jean‐St‐Michel et al determined the beneficial effect of RIPC on whole‐body exercise performance by showing that RIPC can enhance 100‐m swim performance.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…As expected, we also demonstrated that RIPC can enhance exercise endurance during severe‐intensity exercise in this test. Several previous studies have reported the beneficial effect of RIPC on exercise performance, whereas other studies did not observe such effects . Of those, Jean‐St‐Michel et al determined the beneficial effect of RIPC on whole‐body exercise performance by showing that RIPC can enhance 100‐m swim performance.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, McDonald et al reported that RIPC did not enhance exercise performance, as assessed by VO 2 peak and exercise duration during a ramp‐incremental cycling test in patients with heart failure. Moreover, Cocking et al reported that RIPC did not enhance exercise performance, as assessed by power output and exercise distance during a 1‐hour cycling trial in healthy subjects. In these previous studies, McDonald et al recruited patients with heart failure, and Cocking et al set relatively long exercise duration.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In patients with a history of AMI, surgery should only be performed when the illness has been stable for at least 6 mo. In the case of AMI, the blood levels of cardiac Troponin I (cTnI), brain-type natriuretic peptide (BNP) and N-terminal proBNP (NT-proBNP)[29-31] should be evaluated to determine the severity of myocardial injury and heart failure. If the patient has a history of bradycardia, a cardiac pacemaker should be implanted before surgery.…”
Section: Discussionmentioning
confidence: 99%